Comparison of Some Immunological Parameters of Covid-19 Patients with and without Diabetes According to age Groups and Gender - Zaianb Mohammed Madfoon, Musa Nima Mezher, Suhad Mohammed (Pakistan Journal of Medical & Health Sciences, 2022)
During the Covid-19 epidemic, many variables affected the severity of infection, including age, gender, and chronic conditions. In this study, we compared the levels of some immunological parameters (IL6, IFNγ) in Covid 19 patients and diabetic patients with Covid 19 across age groups and gender. Where the levels of interleukin-6 are higher than the normal range when infected with COVID-19 in all age groups and increased in patients without diabetes, where their levels are (210.04 ± 135.44). An increase in the level of IL6 indicates a severe infection with the COVID-19 virus, and this indicates transmission from moderate to severe or severe, as the results of the study did not show any significant differences at P>0.5, and IL6 levels increase in females than in males. Where it reaches (146.105±149.75) The high rate of IFNγ production also indicates support for immunity against infection with the Covid-19 virus, and the equation of its production indicates a low survival rate for patients, as it is produced by helper T cells. JPY 0.009 Where the levels of IFNγ increase significantly in middle ages, reaching (157.64 ± 158.54), and the levels of IFNγ are close between females and males, as they are (102.7 ± 130.27) (102.2 ± 93.12), respectively.